Analysis of Management Behavior on Employee Performance Employee Performance at PT Abcd: Management - Pramukty, Rachmat; Nera Marinda Machdar; Adler Manurung; Wastam Wahyu Hidayat (Dinasti International Journal of Management Science, 2024)
: This research will analyze the relationship between management behavior and employee performance at PT ABCD. This study aims to understand how management behaviors, such as leadership, motivation, and communication, affect employee performance. The purpose in this study is to analyze management behavior on employee performance at PT ABCD. This research uses a qualitative descriptive method with primary data sources through data collection techniques of interviews, observation and documentation. The results in this study indicate that the research conducted an analysis of management behavior at PT Abcd is appropriate or good. Judging from the performance of human resources section, all of which have been systemized and measured clearly and in detail at PT Abcd. clear and detailed at PT Abcd, management behavior analysis in measuring employee performance has a good role in measuring employee performance. measurement of employee performance has a good role in realizing conducive work situation and the implementation of a good and healthy corporate governance system. good and healthy corporate governance system. And is expected to provide useful insight for management of PT ABCD in improving employee performance through improved management behavior. management behavior.